Level Up Your Web Apps With Go - Curtis, Mal (SitePoint, 2015)
Go is an open-source language from Google that's a bit like C. Designed for programmer productivity, it's got a clean syntax, and emphasizes concurrency. This book gives you all you need to use Go in your web applications. You'll learn the basic concepts - language structures, the standard library, and Go tools - then tackle more advanced features like concurrency concepts, testing methodologies, and package structures. At each step, you'll get advice for better coding in Go. You'll see how to structure projects, how to use concurrency effectively, and best practices for testing - as well as many valuable hints and tips gleaned from real world experience of developing web applications with Go. You'll learn: Get to grips with Go language basics (types, the standard library, tools) Use Go with HTTP Work with images Understand concurrency Test effectively Master deployment And much more ...